2019
DOI: 10.1021/acs.jafc.9b06618
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic Investigation of the Interplay between Enzymatic Tenderization and the Digestibility of Beef Semimembranosus Proteins

Abstract: This work investigated the influence of enzymatic tenderization on digestibility changes of beef semimembranosus proteins using peptidomics methods. Hydrolysis by proteinase K and bromelain elevated the average bitterness index of identified peptides by generating high-Q values peptides (1714–1790 Cal/mol), including KDLFDPIIQ, LIDDHFLFDKPVSPL, and QLIDDHFLFDKPVSPLLL. Proteolysis during enzymatic tenderization acted as a “pre-digestion” step and significantly elevated the degree of hydrolysis of beef protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…The peptides after gastrointestinal digestion were identified with the peptidomics method . Each 0.1 mL gastrointestinal digestion sample was mixed with equal volumes of 0.2% formic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptides after gastrointestinal digestion were identified with the peptidomics method . Each 0.1 mL gastrointestinal digestion sample was mixed with equal volumes of 0.2% formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of hydrolysis (DH) was used to evaluate protein digestibility, and DH was determined following a previous work. 17 First, the digestants (75 μL) were mixed with an equal volume of TCA (24%), followed by precipitation in ice water for 30 min. Then, the mixture was centrifuged at 4000g (4 °C, 20 min).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolysis induced by exogenous proteases will change the composition, cleavage sites, and digestibility of the target protein to generate bioactive peptides (Lafarga & Hayes 2014). However, few studies have correlated enzymatic tenderisation with meat nutrition, a subject that deserves further investigation (Zhao et al 2020).…”
Section: Enzymatic Techniquesmentioning
confidence: 99%
“… Xue et al (2020) reported that structural changes through autoclaving affect the digestion of meat. It has been reported that proteolysis due to enzymatic tenderizing weakens the protein structure and can increase digestibility by increasing protein accessibility to digestive proteases ( Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%